2014
DOI: 10.1111/phpp.12125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of psoralen + sunlight vs. combination of isotretinoin and psoralen + sunlight for the treatment of chronic plaque‐type psoriasis vulgaris: a randomized hospital‐based study

Abstract: The combination of isotretinoin with PUVAsol is more effective compared with PUVAsol alone for treating chronic plaque psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Patients were then started on oral PUVAsol therapy. In the absence of a standard protocol for PUVAsol, the most frequently followed protocol was selected which is described below [ 15 ]. For oral PUVAsol, 8-methoxypsoralen (8-MOP) was administered orally in morning with breakfast followed by sunlight exposure, after an interval of 2 hours on 3 alternate days in a week.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were then started on oral PUVAsol therapy. In the absence of a standard protocol for PUVAsol, the most frequently followed protocol was selected which is described below [ 15 ]. For oral PUVAsol, 8-methoxypsoralen (8-MOP) was administered orally in morning with breakfast followed by sunlight exposure, after an interval of 2 hours on 3 alternate days in a week.…”
Section: Methodsmentioning
confidence: 99%
“…Gahalaut et al 11 in a PP analysis of 40 patients of psoriasis treated with PUVA sol observed that 20 per cent of their patients achieved PASI 75, 40 per cent achieved PASI 50, while 10 per cent had an aggravation of their disease at 12 wk. The response of psoriasis to PUVA sol is enhanced by the concomitant use of retinoids 12 . Kar et al 13 reported complete clearance of CPP in 32 per cent patients and more than 50 per cent improvement in 44 per cent of patients treated with PUVA sol for eight weeks.…”
Section: Discussionmentioning
confidence: 99%
“… 91 The second study showed that combining isotretinoin (0.5 mg/kg/day) with oral psoralen + sun exposure (PUVAsol) is more effective than PUVAsol alone for treating chronic plaque psoriasis. 92 A case series documented that five individuals with generalized pustular psoriasis did not respond to conventional therapy but were effectively treated with isotretinoin (1.5–2 mg/kg/day) within a short treatment period. 93 A comparative study revealed that even though the efficacy of isotretinoin and etretinate in treating generalized pustular psoriasis was comparable, isotretinoin was less effective than etretinate in treating chronic plaque psoriasis.…”
Section: Introductionmentioning
confidence: 99%